2018
DOI: 10.1017/s1368980017003986
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean diet, an environmentally friendly option: evidence from the Seguimiento Universidad de Navarra (SUN) cohort

Abstract: In this Mediterranean cohort, better adherence to the MedDiet was an eco-friendly option according to resource consumption and GHG emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 66 publications
3
57
0
2
Order By: Relevance
“…These considerations are in line with the results from the few reports using empirical data from cohort studies. A previous study conducted on the SUN cohort (including Spanish individuals) sharing similar methodology showed that better adherence to the Mediterranean diet was associated with lower land use, water consumption, energy consumption, and GHG emissions in a linear manner [32]. In a prospective observation, the findings were confirmed, as both a Mediterranean and a pro-vegetarian dietary pattern would exert the best health benefits and the lowest environmental effects; notably, the Western pattern was the most affordable while the Mediterranean pattern was the most expensive choice [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations are in line with the results from the few reports using empirical data from cohort studies. A previous study conducted on the SUN cohort (including Spanish individuals) sharing similar methodology showed that better adherence to the Mediterranean diet was associated with lower land use, water consumption, energy consumption, and GHG emissions in a linear manner [32]. In a prospective observation, the findings were confirmed, as both a Mediterranean and a pro-vegetarian dietary pattern would exert the best health benefits and the lowest environmental effects; notably, the Western pattern was the most affordable while the Mediterranean pattern was the most expensive choice [40].…”
Section: Discussionmentioning
confidence: 99%
“…The environmental impact of the food items collected in the FFQ was based on a dataset previously described [32]. Briefly, the assessment of the natural resources (i.e., water, land, and energy) use and GHG emissions of each food product had been assessed based on secondary data, collected from several scientific sources (please see Supplementary Materials) [32]. The system boundaries had been food production and processing (except for land use, which included crops and livestock production, but not land related to food processing).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…The effect of adherence to the MD on water use and GHG found in this study corroborates with findings of reports from other countries which showed similar negative associations of adherence to the MD with water use and GHGs. For instance, in Spain, an analysis of EFPs associated with food consumption among 20,363 adults showed that better adherence to the MD was associated with lower water use and GHG emissions [14]. A study in Italy showed that adherence to the MD would result not only in health benefits but also significant reductions in the environmental food footprint on natural resources, especially water consumption [50].…”
Section: Discussionmentioning
confidence: 99%
“…Food production, distribution, and consumption are arguably the major human activities with a direct impact not only on human health but also on environmental sustainability [11]. Environmental footprints (EFPs) characterized by land, water, and energy use, along with greenhouse gas (GHG) emissions, are the major environmental impacts of personal food consumption and are expected to become even more prominent with the rapidly growing human population [12][13][14]. As such, both health and environmental perspectives need to be accounted for when re-forming food systems and dietary patterns [1,[15][16][17], giving rise to the notion of sustainable diets.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily because the production of animal-derived foods, especially beef, generate a bigger carbon footprint than the production of plant foods [22]. In fact, among those who consume animal-based products, these foods are the major contributors to the carbon footprint of their diets [23].…”
Section: Introductionmentioning
confidence: 99%